Knowledge, attitude and practices on cervical cancer screening among undergraduate female students in University of Gondar, Northwest Ethiopia: an institution based cross sectional study - Alem Getaneh; Birhanemeskel Tegene; Teshome Belachew (BMC, 2021)
Abstract Background Cervical cancer is a major public health problem. In the world, cervical cancer is the fourth most common cancer among women and it is one of the leading causes of cancer mortality in females. It is the second most common women cancer in Ethiopia with almost 6300 new cases and 4884 deaths annually. Despite the high burden of new cases and deaths, there is a scarcity of data on knowledge, attitude and practices (KAP) towards cervical cancer screening among female university students in Ethiopia particularly in the study area. Therefore, the present study was aimed to assess the KAP of undergraduate female students towards cervical cancer screening. Methods An institution based cross-sectional study was conducted in April 2018 at the University of Gondar, College of Medicine and Health Sciences undergraduate female students. Pretested, self-administered questionnaire was used for data collection. Four hundred and three female students were recruited by a simple random sampling method and the data were entered and analyzed using SPSS version 20 statistical packages. Descriptive data analysis was used to report the results. Results More than half of the respondents (59.3.3%) had good knowledge, whereas nearly 67.7% of the respondents had favorable attitude towards cervical cancer. However, less than 1% of the respondents had been screened for cervical cancer. Conclusion Although undergraduate female students had apparently good knowledge and favorable attitude, their practices on cervical cancer screening were quite low. Therefore, the health sectors and the gender streaming office of the university mobilize students to strengthen the uptake the cervical cancer screening practice.